HspB8 mutation causing hereditary distal motor neuropathy impairs lysosomal delivery of autophagosomes. - Kwok, A; Phadwal, K; Turner, B; Oliver, P; Raw, A; Simon, A; Talbot, K; Agashe, V (2011)
HspB8, a small heat-shock protein implicated in autophagy, is mutated in patients with distal hereditary motor neuropathy type II (dHMNII). Autophagy is essential for maintaining protein homeostasis in the central nervous system, but its role has not been investigated in peripheral motor neurons. We used a novel, multispectral-imaging flow cytometry assay to measure autophagy in cells. This assay revealed that over-expression of wild-type HspB8 in motor neuron-like NSC34 cells led to an increased co-localisation of autophagosomes with the lysosomes. By contrast, over-expression of mutant HspB8 resulted in autophagosomes that co-localised with protein aggregates but failed to co-localise with the lysosomes. A similar impairment of autophagy could also be demonstrated in peripheral blood mononuclear cells from two dHMNII patients with the HspB8(K141E) mutation. We conclude that defects in HspB8-mediated autophagy are likely to contribute to dHMNII pathology and their detection in peripheral blood mononuclear cells could be a useful, accessible biomarker for the disease.